Biotribology in Arthroplasty: Worn Surfaces Investigation on Ceramic Hip Femoral Heads Considering Wettability - Saverio Affatato; Alessandro Ruggiero (Applied Sciences, 2020)
Ceramic-on-ceramic bearings for total hip replacement are considered the best choice to avoid problems such as osteolysis and wear, mainly related to soft bearings. The aim of this work was to investigate in a comparative way different kinds of ceramic femoral heads for total hip replacements from a biotribological point of view, discussing the results obtained in terms of topographies, presence of metal transfer (MT) phenomena, and wettability on their worn surfaces in a tribological framework. Different ceramic femoral heads derived from in vitro wear tests, retrieved form patients, and brand new total hip replacements were investigated. The patients group had an average age of 60 years (ranging from 27 to 83). In most cases, the cause of failure was aseptic loosening of the acetabular component. Roughness analyses were performed to measure the tribological surface evolution of the material; an SEM and EDS investigation on the explanted heads proves and quantified MT, while the wettability was measured through a novel optical laboratory set-up with the aim to furnish useful data in the framework of synovial lubrication phenomena acting in the tribosystem. For the average roughness measurements on explanted specimens were considered three parameters (Ra = the average area between the roughness profile and its mean line; Rt = the vertical distance from the deepest valley to the highest peak of the roughness profile; and Rsk = it is the skewness and it is a measure of the asymmetry of the amplitude distribution function. In other words, the skewness indicates whether a surface is dominated by peaks or by valleys) and their values were: Ra 0.22 ± 0.12 μm, Rt 34.5 ± 13.5 μm and Rsk −0.01 ± 11.3; on the new specimens we measured Ra 0.01 ± 0.001 μm, Rt 0.12 ± 0.09 μm, and Rsk = 5.67 ± 8.7; for the in vitro specimens they were Ra 0.05 ± 0.12 μm, Rt 0.71 ± 1.4 μm and Rsk 7.73 ± 20.6. The wettability angle measurements showed hydrophilic surfaces for all femoral heads considered in this study with small differences between the three investigated categories, allowing to discuss their effects on the biobearings’ lubrication phenomena.